2018
DOI: 10.1016/j.jinorgbio.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A combined computational and experimental study on selective flucloxacillin hydroxylation by cytochrome P450 BM3 variants

Abstract: The 5'-hydroxymethyl metabolite of the penicillin based antibiotic flucloxacillin (FLX) is considered to be involved in bile duct damage occurring in a small number of patients. Because 5'-hydroxymethyl FLX is difficult to obtain by organic synthesis, biosynthesis using highly active and regioselective biocatalysts would be an alternative approach. By screening an in-house library of Cytochrome P450 (CYP) BM3 mutants, mutant M11 L437E was identified as a regioselective enzyme with relatively high activity in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…73 The MD trajectory and structure file formats are imported using the MDTraj library. 74 MD trajectories were analyzed for the following biomolecular interaction types at a 100 ps resolution similar to previous studies performed by us: 35,61,75 Hydrophobic interactions : identified as all contacts between carbon atoms within 0.4 nm having only C or H atoms as neighbors. Interacting pairs from the same source atom to multiple target atoms in the same residue, in both directions, were filtered to retain only the pair with the smallest distance.…”
Section: Methodsmentioning
confidence: 99%
“…73 The MD trajectory and structure file formats are imported using the MDTraj library. 74 MD trajectories were analyzed for the following biomolecular interaction types at a 100 ps resolution similar to previous studies performed by us: 35,61,75 Hydrophobic interactions : identified as all contacts between carbon atoms within 0.4 nm having only C or H atoms as neighbors. Interacting pairs from the same source atom to multiple target atoms in the same residue, in both directions, were filtered to retain only the pair with the smallest distance.…”
Section: Methodsmentioning
confidence: 99%
“…All MD simulations (including thermal equilibration and 100 ns production simulations) were performed using identical simulation settings and force-field parameters for the protein and heme group (either in the resting or the compound Is tate) as described in ref. [74]. Atomic coordinates were written out to disk every 100 ps.…”
Section: Methodsmentioning
confidence: 99%
“…5′‐HM‐FLX was obtained biosynthetically by hydroxylation of flucloxacillin using a drug metabolizing mutant of CYP102A1 from Bacillus megaterium , M11 L437E, which contains mutations R47L, E64G, F81I, F87V, E143G, L188Q, E267V, G415S and L437E compared to wild‐type CYP102A1. This mutant appeared to selectively convert flucloxacillin to 5′‐HM‐FLX (Luirink et al ., ); 1 mL of a solution of 100 mM flucloxacillin in DMSO was added to 49 mL 100 mM potassium phosphate buffer pH 7.4 and incubated in the presence of 1 ÎźM of M11 L437E and a NADPH‐regenerating system (NRS) for 20 h at room temperature with constant stirring. The NRS was consisted of 100 ÎźM NADPH, 10 mM glucose‐6‐phosphate and 0.5 units¡mL −1 glucose‐6‐phosphate dehydrogenase (final concentrations).…”
Section: Methodsmentioning
confidence: 99%